ANALISIS PENGARUH PDRB, INFLASI, NILAI KURS, DAN TENAGA KERJA TERHADAP PENERIMAAN PAJAK PADA KABUPATEN CILACAP, BANYUMAS, PURBALINGGA, KEBUMEN DAN PURWOREJO - Mispiyanti, Mispiyanti; Kristanti, Ika Neni (P4M STIE Putra Bangsa, 2018)
Taxes serve to reduce inequalities among the population and thus demand substantial government expenditures for state financing which one of the sources is tax revenue. Butmany factors affect the high low tax revenue. This study aims to determine partially whether the GDP, inflation, the exchange rate of rupiah against US Dollar and labor have a positive effect on tax revenues and also to determine whether GRDP, inflation, the exchange rate of rupiah against US Dollar and labor in together have a positive effect on tax revenue. This study uses data realization of tax revenue, GDP data, inflation data, and employment data in the districts of Cilacap, Banyumas, Purbalingga, Kebumen, Purworejo as well as data on the Rupiah exchange rate against US Dollar. The results show that partially PDRB and labor positively affect the tax revenue while inflation and the exchange rate of rupiah against US Dollar have no positive effect on tax revenue. In together the variables PDRB, inflation, exchange rate and labor, significantly affect the variable tax revenue.   Keywords: tax revenue, GRDP, inflation, US Dollar exchange rate, labor